PENGEMBANGAN POTENSI EKOWISATA BERBASIS MASYARAKAT DI NAGARI KANDANG BARU KABUPATEN SIJUNJUNG PROPINSI SUMATERA BARAT - Rani Pratama Putri; Dodon Yendri (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2019)
Kandang Baru is one of 61 development villages in Sijunjung Regency, West Sumatra Province. The location is very strategic on the trans-Sumatra road, which is the main route connecting the provinces of West Sumatra and Jambi so that it supports the potential and bright prospects in developing economic and socio-cultural development, especially in the tourism sector. This village has good tourism and natural resource potential but has not been exploited either by the government or the local community. With the 2019 PPM Andalas University KKN activities aimed at developing human resources and community empowerment efforts through various creative and innovative work programs, it is expected that the potential can be developed. This activity is carried out with a causal method, which is to carry out work programs based on a SWOT analysis of problems that occur, such as low levels of education, low welfare of the population, conditions of primary schools that are expected, and so on. The results of this activity are summarized in physical and non-physical forms. Physically KKN students succeeded in initiating the construction of the Bukit Capang Tigo geopark tourism area gate (BCT) and have stood beautifully in the area, holding a reading park for elementary students by utilizing the nagari library and other programs. Non-physically, character building is carried out through tutoring, fostering camp tahfidz, and non-physical tourism development in BCT geopark tourism promotion by utilizing social media @KandangBaru Traveling through KKN activities conducted for 40 days, students have succeeded in contributing to Kandang New as a form of community service.